The Effect of Religious Relaxation Therapy on Improving Sleep Quality of Patients Chronic Kidney Failure: A Pilot Study in Surabaya (Bangladesh Journal of Medical Science, 2019)
Objective: It is discovered that approximately 80% patients with chronic kidney failure undergoing haemodialysis treatment experience a difficulty to sleep. Such issue could decrease the patients’ living quality. The relaxation therapy using spiritual approach based on the patients’ religion to improve sleep quality has not been scientifically proven yet. This study aims to analyze the effect of religious relaxation therapy on patients with chronic kidney failure undergoing haemodialysis treatment.Materials and methods: The research was quasy experiment with prepost test control group design. The subjects of the research are the entire patients with chronic kidney failure who undergo haemodialysis treatment in the Islamic Hospital. The samples are taken from sixty clients recruited by random sampling allocation technique. Those clients aged 20-65 years old, Moslem and no complications. Patients’ sleeping quality is determined by The Pittsburgh Sleep Quality Index (PSQI). Meanwhile, the data is analyzed by using Wilcoxon sign rank statistic test and Mann Whitney U test.Results and Discussion: The research showed that the religious relaxation therapy is proven to have a more improved good sleep quality (73.3 %) while the control group tends to be stagnant. The religious therapy is proven to have a positive effect on sleep quality by p = 0.000Conclusion: The religious relaxation therapy gives positive effects in improving the sleep quality for patients with chronic kidney failure who undergo haemodialysis treatment.Bangladesh Journal of Medical Science Vol.19(1) 2020 p.48-52